Estimating wastewater dilution using chemical markers and incomplete flow measurements: Application to normalisation of SARS-CoV-2 measurements - Owen D. Jones; Amy J. Baldwin; Isabelle Durance; William B. Perry; Andrew Weightman (Journal of Water Process Engineering, 2026)

Integrating science for water security governance - Kristen M. Whitney; Rebecca M. Peters; Anil Mishra; Annalise G. Blum; Perry C. Oddo; Kate A. Brauman; Angelica L. Gutierrez; John D. Bolten; Matthew J. McCarthy; Andrés Sánchez (Global Environmental Change, 2026)

Assessing hydrochar wash-water toxicity: screening strategies for reducing toxicity from food waste-derived hydrochars - Andres Sarrion; Jasmine R. Flora; Joseph R.V. Flora; Ramesh Goel; Lubo Liu; Perry J. Pellechia; Elena Diaz; Angel F. Mohedano; Nicole D. Berge (Waste Management, 2026)

Prioritising actions over space and time in multi-habitat ecological restoration: Insights from indicator species in coastal seascapes - Ben L. Gilby; Andrew D. Olds; Michael Sievers; Maria L. Vozzo; Brittany B. Elliott; Lucy A. Goodridge Gaines; Jesse D. Mosman; Hannah J. Perry; Ashley J. Rummell; Christopher J. Henderson (Landscape and Urban Planning, 2026)

The northern California current on fire: consequences of a widespread and persistent anomalous pyrosome bloom - Richard D. Brodeur; Dylan G.E. Gomes; Douglas L. Draper; Elizabeth A. Daly; Samantha M. Zeman; Moira Galbraith; R. Ian Perry; James J. Ruzicka; Roxanne R. Robertson (Progress in Oceanography, 2026)

Cryptic coral reef microhabitats and the functional role of brittle stars in biogenic sediment generation - D. M. de Bakker; C. T. Perry; L. de Nooijer; A. J. Ramírez-Menéndez; J. E. Lloyd Newman; F. Hale; L. Alvarez-Filip (Coral Reefs, 2026)
Recent studies have highlighted the ecological importance of cryptic habitat space on coral reefs. These microhabitats, ranging from framework cavities to intra-branch space within marine macroalgae, can harbour diverse and ecologically relevant taxa. Here we show that brittle stars, ubiquitous across such cryptic habitats (reported densities exceeding 100 ind. m −2 ), represent an important, but previously neglected, source of skeletal sediment on reefs. Reef-derived carbonate sediment is generated by a range of reef biota and represents a critical geo-ecological process, contributing to reef structural development and vertical accretion via framework infilling, and the development and maintenance of lagoonal and shoreline habitats. Our sediment production estimates are based on skeletal carbonate content data for differently sized specimens of common brittle star morphotypes, combined with field-based density assessments from widespread microhabitat types (framework cavities, sub-rubble space and intra-algal skeletal branches) on Mexican Caribbean reefs. Resulting estimates suggest that brittle stars can make substantial contributions to reef sediment production (averaging 110 g m⁻ 2 yr⁻ 1 ; 95% CI 59–161). Spine-bearing taxa contribute disproportionately due to their high skeletal mass (> 6 g in large individuals) and high abundance (accounting for over 80% of sub-rubble populations). Resultant biogenic sediments are high-Mg calcite (15.6 ± 0.1 mol% MgCO₃) and predominantly disarticulate into fine to coarse-grained sand material (125 µm–2 mm). These findings highlight the underappreciated role of brittle stars in reef carbonate cycling. With many reef systems undergoing rapid changes in benthic ecology and microhabitat space availability, identifying and characterising links to biogenic sediment sources is central to understanding future reef sediment production regimes.

CRISPR Epigenome Editing of IL1R1 Expression of Neurons that Innervate the Temporomandibular Joint or Knee Causes Reduced Sensitization to Osteoarthritic Environment - Joshua D. Stover; Robby D. Bowles; Yenisel Cruz-Almeida; Robert M. Caudle; Kyle D. Allen; Armen Akopian; Benjamin Arenkiel; Basak Ayaz; Yangjin Bae; Bruna Balbino de Paula; Anita Bandrowski; Mario Danilo Boada; et al. (Annals of Biomedical Engineering, 2026)

Passive environmental DNA (eDNA) sampling is effective for monitoring vessel biofouling in the Southern Ocean - Frances Perry; Justine D. Shaw; Phillip Cassey; Ashley Coutts; Patrick N. Lewis; Anna J. MacDonald; Andrea M. Polanowski; Jonathan S. Stark; Leonie Suter (Science of The Total Environment, 2026)

Quantifying coral reef carbonate budgets: a comparison between ReefBudget and CoralNet - Sivajyodee Sannassy Pilly; Joseph E. Townsend; Cut Aja Gita Alisa; Tries B. Razak; Ronan C. Roche; John R. Turner; Stephen Chan; David J. Kriegman; Andreas J. Andersson; Chris T. Perry; Ines D. Lange; Travis A. Courtney (Coral Reefs, 2025)
Calcium carbonate production constitutes one of the core processes that drive coral reef ecosystem functioning and can be assessed using in-water or image-based survey methods, which have not previously been compared. This study compares carbonate production estimates from in-water ReefBudget surveys and image-based CoralNet analyses in Puerto Rico, Indonesia, and Chagos Archipelago. Methods were compared for different regions (Western Atlantic and Indo-Pacific), reef settings (low and high coral cover), CoralNet calcification versions (v1 and v2), and input metrics (regional vs. local coral growth rates). We show similar gross carbonate production estimates between methods, indicating that area-normalised scaling of calcification rates and assumptions about colony size and rugosity employed in CoralNet produce comparable estimates to ReefBudget surveys. Divergences in carbonate production estimates are potentially driven by differences in survey methods (reef contour measurements vs. planar imagery) and survey effort, which affect calcifier cover estimates, particularly at low coral cover sites. Local versus regional growth rate comparisons suggest site-specific factors can influence accuracy more than method choice. Our findings suggest that image-based methods can allow rapid reef-scale calcification estimates from photo or video imagery. These methods, combined with machine learning substrate classification algorithms, can estimate both benthic cover and carbonate production over larger reef areas and can be applied to historically collect benthic cover data to track carbonate production trends. We encourage researchers to recognise situation-specific differences in methodologies and select the one most suitable for their specific study site, required level of accuracy, and time constraints for fieldwork and image analysis.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Exposure to residential greenness, perceived stress, and depressive symptoms in a North American preconception cohort - Cameron J. Reimer; Mary D. Willis; Amelia K. Wesselink; Perry Hystad; Erin J. Campbell; Elizabeth E. Hatch; Kipruto Kirwa; Jaimie L. Gradus; Marco Vinceti; Lauren A. Wise; Marcia Pescador Jimenez (Environmental Research, 2024)

Dust in the Critical Zone: North American case studies - J. Brahney; R.C. Heindel; T.E. Gill; G. Carling; J.M. González-Olalla; J. Hand; D.V. Mallia; J.S. Munroe; K. Perry; A.L. Putman; S.M. Skiles; B.R. Adams; et al. (Earth-Science Reviews, 2024)

Quantifying Environmental and Spatial Patterns of Fish on Log Snags to Optimise Resnagging in Coastal Seascapes - Lucy A. Goodridge Gaines; Jesse D. Mosman; Christopher J. Henderson; Andrew D. Olds; Hannah J. Perry; Ben L. Gilby (Estuaries and Coasts, 2024)
Long-term declines in coastal water quality and sedimentation can affect the restoration success of ecosystems such as seagrass and shellfish reefs. Resnagging coastal seascapes offers a potential alternative restoration method that is not reliant on abiotic conditions and which may enhance degraded landscapes for fish and fisheries. While common in freshwater ecosystems, such interventions are unusual for coastal seascapes despite log snags supporting significant benefits for coastal fish. In this study, we identify the spatial (e.g. seascape connectivity), habitat condition (e.g. log snag complexity and food availability) and water quality variables that best explain variation in fish assemblages on log snags to help prioritise the placement and design of resnagging efforts in estuaries. We surveyed fish assemblages on log snags using underwater videography at 363 sites across 13 estuaries in southeast Queensland, Australia, over 3 years. Sites less than 10,000 m from the estuary mouth, more than 2500 m from urban structures and located in water depths of < 3 m harboured more diverse fish assemblages. Sites less than 10,000 m from the estuary mouth with lower (< 25%) algae cover harboured greater total fish abundance and harvested fish abundance. Similar trends were found for the abundance of individuals from key functional groups, although these trends were mediated by other seascape contexts (e.g. the area of natural habitat) and water quality variables (e.g. chlorophyll-a concentration and dissolved oxygen saturation). Our results indicate that log snag placement in estuaries for benefits to fish and fisheries can be maximised if sites are planned strategically.

Sustainable mining in tropical, biodiverse landscapes: Environmental challenges and opportunities in the archipelagic Philippines - Justine Perry T. Domingo; Gawen R.T. Jenkin; Laura Quick; Richard D. Williams; Karen A. Hudson-Edwards; Cecilia Tortajada; Patrick Byrne; Tom J. Coulthard; Jenielyn T. Padrones; Rich Crane; Cris Reven L. Gibaga; Grigorios Vasilopoulos; et al. (Journal of Cleaner Production, 2024)

Within-field extrapolation away from a soil moisture probe using freely available satellite imagery and weather data - R. G. V. Bramley; E. M. Perry; J. Richetti; A. F. Colaço; D. J. Mowat; C. E. M. Ratcliff; R. A. Lawes (Precision Agriculture, 2024)
Recognition of the importance of soil moisture information to the optimisation of water-limited dryland cereal production has led to Australian growers being encouraged to make use of soil moisture sensors. However, irrespective of the merits of different sensing technologies, only a small soil volume is sensed, raising questions as to the utility of such sensors in broadacre cropping, especially given spatial variability in soil water holding capacity. Here, using data collected from contrasting sites in South Australia and Western Australia over two seasons, during which either wheat or barley were grown, we describe a method for extrapolating soil moisture information away from the location of a probe using freely-available NDVI time series and weather data as covariates. Relationships between soil moisture probe data, cumulative NDVI (ΣNDVI), cumulative net precipitation (ΣNP) and seasonal growing degree days (GDD) were significant ( P < 0.0001). In turn, these could be used to predict soil moisture status for any location within a field on any date following crop emergence. However, differences in ΣNDVI between different within-field zones did not fully explain differences in the soil moisture from multiple sensors located in these zones, resulting in different calibrations being required for each sensor or zone and a relatively low accuracy of prediction of measured soil moisture (R 2 adj ~ 0.4–0.7) which may not be sufficient to support targeted agronomic decision-making. The results also suggest that at any location within a field, the range of variation in soil moisture status down the soil profile on any given date will present as greater than the spatial variation in soil moisture across the field on that date. Accordingly, we conclude that, in dryland cereal cropping, the major value in soil moisture sensors arises from an enhanced ability to compare seasons and to relate similarities and differences between seasons as a guide to decision-making.

Flood effects on estuarine fish are mediated by seascape composition and context - Christopher J. Henderson; Andrew D. Olds; Lucy A. Goodridge Gaines; Jesse D. Mosman; Hannah J. Perry; Hayden P. Borland; Ben L. Gilby (Marine Biology, 2024)
Estuaries are crucial feeding, nursery and resting sites for fish but can also be subject to the impacts of severe flooding. The environmental features of estuaries can mediate how they respond to these impacts. For example, the size, configuration, and context of estuarine habitats across seascapes affects the value of patches for fish, and so fish assemblages at sites with a greater habitat extent or closer to the mouth of an estuary may rebound more quickly from flooding. We investigated how a once in 100-year flood event affected fish assemblages at approximately 600 sites across 13 estuaries and six estuarine habitats (bare sediments, log snags, mangrove forests, rocky structures, saltmarsh and seagrass meadows) in southeast Queensland, Australia, and determined whether flood impacts were mediated by the position of sites within the broader estuarine seascape. Sites were surveyed annually in 2020/2021 (pre-flood) and 2022 (6 months post-flood) using underwater videography. Flooding modified the structure of the fish community and reduced the abundance of fish targeted by local fisheries in all six habitats. Crucially, flood effects on fish were greater at sites near more expansive urbanisation in some ecosystems, but lower at sites nearer to the estuary mouth. Maximising the extent of natural habitats across estuaries can mediate the effects of floods and should be priorities for restoration and management plans seeking to maintain biodiversity and fisheries productivity in the face of increasing climate-related disturbances.

Using parentage-based tagging to estimate survival of Chinook salmon fry in a large storage reservoir - Adam C. Pope; Tobias J. Kock; Russell W. Perry; Karen M. Cogliati; Kathleen G. O’Malley; Christina A. Murphy; Dalton J. Hance; Scott D. Fielding (Environmental Biology of Fishes, 2024)

Ambient air pollution and rate of spontaneous abortion - Amelia K. Wesselink; Kipruto Kirwa; Perry Hystad; Joel D. Kaufman; Adam A. Szpiro; Mary D. Willis; David A. Savitz; Jonathan I. Levy; Kenneth J. Rothman; Ellen M. Mikkelsen; Anne Sofie Dam Laursen; Elizabeth E. Hatch; et al. (Environmental Research, 2024)

A cloudy forecast for species distribution models: Predictive uncertainties abound for California birds after a century of climate and land‐use change - John D. J. Clare; Perry de Valpine; Diana A. Moanga; Morgan W. Tingley; Steven R. Beissinger (Global Change Biology, 2024)
Correlative species distribution models are widely used to quantify past shifts in ranges or communities, and to predict future outcomes under ongoing global change. Practitioners confront a wide range of potentially plausible models for ecological dynamics, but most specific applications only consider a narrow set. Here, we clarify that certain model structures can embed restrictive assumptions about key sources of forecast uncertainty into an analysis. To evaluate forecast uncertainties and our ability to explain community change, we fit and compared 39 candidate multi‐ or joint species occupancy models to avian incidence data collected at 320 sites across California during the early 20th century and resurveyed a century later. We found massive (>20,000 LOOIC) differences in within‐time information criterion across models. Poorer fitting models omitting multivariate random effects predicted less variation in species richness changes and smaller contemporary communities, with considerable variation in predicted spatial patterns in richness changes across models. The top models suggested avian environmental associations changed across time, contemporary avian occupancy was influenced by previous site‐specific occupancy states, and that both latent site variables and species associations with these variables also varied over time. Collectively, our results recapitulate that simplified model assumptions not only impact predictive fit but may mask important sources of forecast uncertainty and mischaracterize the current state of system understanding when seeking to describe or project community responses to global change. We recommend that researchers seeking to make long‐term forecasts prioritize characterizing forecast uncertainty over seeking to present a single best guess. To do so reliably, we urge practitioners to employ models capable of characterizing the key sources of forecast uncertainty, where predictors, parameters and random effects may vary over time or further interact with previous occurrence states.

Drivers of Ecological Condition Identify Bright Spots and Sites for Management Across Coastal Seascapes - Ben L. Gilby; Lucy A. Goodridge Gaines; Hayden P. Borland; Christopher J. Henderson; Jesse D. Mosman; Andrew D. Olds; Hannah J. Perry (Estuaries and Coasts, 2023)
Disentangling natural and anthropogenic effects on ecosystem condition can uncover bright spots in urban landscapes that are performing above expectations and so are potential sites for conservation or benchmarking, as well as sites performing below expectations that should be the focus of management. In this study, we tested for correlations between metrics indexing ecological condition (focusing on habitat-forming species) and a suite of spatial and environmental variables at 373 sites across four ecosystems (mangroves, seagrass, saltmarsh and rocky outcrops) and 13 estuaries in southeast Queensland, Australia. Ten condition metrics across the four ecosystems correlated with variables indexing the seascape context of sites, with condition metrics typically higher at sites more connected to natural features including the estuary mouth and mangroves. Urbanisation affected only two metrics, with rocky outcrop oyster cover being 75% lower at sites near extensive urbanisation and algae cover being highest at sites with intermediate urbanisation. We identified patterns in at least two variables from each ecosystem, meaning that decisions need to be made regarding optimal ecosystem states. Overall, management sites were more common than bright spots, with 50% more management sites in mangroves, 42.8% more in seagrasses, 38.5% more in saltmarshes and no bright spots in rocky outcrops (however, 10.3% of rocky outcrop sites were bright spots under an alternate ecosystem state model). We found that patterns in habitat condition across coastal seascapes can be predicted using spatial modelling approaches, and that these models can be readily used to prioritise management actions across the entire regions.

Identifying optimal values of coastal habitat condition for management and restoration - Hannah J. Perry; Lucy A. Goodridge Gaines; Hayden P. Borland; Christopher J. Henderson; Andrew D. Olds; Jesse D. Mosman; Ben L. Gilby (Estuarine, Coastal and Shelf Science, 2023)

Seasonal differences in day-roost selection by Northern long-eared bats (Myotis septentrionalis) in Louisiana and a meta-analytical comparison across North America - Carlos J. Garcia; David A. Ray; Roger W. Perry; Richard D. Stevens (Forest Ecology and Management, 2023)

Improving sightings-derived residency estimation for whale shark aggregations: A novel metric applied to a global data set - Gonzalo Araujo; Ariana Agustines; Steffen S. Bach; Jesse E. M. Cochran; Emilio de la Parra-Galván; Rafael de la Parra-Venegas; Stella Diamant; Alistair Dove; Steve Fox; Rachel T. Graham; Sofia M. Green; Jonathan R. Green; et al. (Frontiers in Marine Science, 2022)
The world’s largest extant fish, the whale shark Rhincodon typus , is one of the most-studied species of sharks globally. The discovery of predictable aggregation sites where these animals gather seasonally or are sighted year-round – most of which are coastal and juvenile-dominated – has allowed for a rapid expansion of research on this species. The most common method for studying whale sharks at these sites is photographic identification (photo-ID). This technique allows for long-term individual-based data to be collected which can, in turn, be used to evaluate population structure, build population models, identify long-distance movements, and assess philopatry and other population dynamics. Lagged identification rate (LIR) models have fewer underlying assumptions than more traditional capture mark recapture approaches, making them more broadly applicable to marine taxa, especially far-ranging megafauna species like whale sharks. However, the increased flexibility comes at a cost. Parameter estimations based on LIR can be difficult to interpret and may not be comparable between areas with different sampling regimes. Using a unique data-set from the Philippines with ~8 years of nearly continuous survey effort, we were able to derive a metric for converting LIR residency estimates into more intuitive days-per-year units. We applied this metric to 25 different sites allowing for the first quantitatively-meaningful comparison of sightings-derived residence among the world’s whale shark aggregations. We validated these results against the only three published acoustic residence metrics (falling within the ranges established by these earlier works in all cases). The results were then used to understand residency behaviours exhibited by the sharks at each site. The adjusted residency metric is an improvement to LIR-based population modelling, already one of the most widely used tools for describing whale shark aggregations. The standardised methods presented here can serve as a valuable tool for assessing residency patterns of whale sharks, which is crucial for tailored conservation action, and can cautiously be tested in other taxa.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Wave exposure shapes reef community composition and recovery trajectories at a remote coral atoll - Ines D. Lange; Cassandra E. Benkwitt; Jamie M. McDevitt-Irwin; Kristina L. Tietjen; Brett Taylor; Mark Chinkin; Rachel L. Gunn; Melissa Palmisciano; Margaux Steyaert; Bry Wilson; Holly K. East; John Turner; et al. (Coral Reefs, 2021)
In a time of unprecedented ecological change, understanding natural biophysical relationships between reef resilience and physical drivers is of increasing importance. This study evaluates how wave forcing structures coral reef benthic community composition and recovery trajectories after the major 2015/2016 bleaching event in the remote Chagos Archipelago, Indian Ocean. Benthic cover and substrate rugosity were quantified from digital imagery at 23 fore reef sites around a small coral atoll (Salomon) in 2020 and compared to data from a similar survey in 2006 and opportunistic surveys in intermediate years. Cluster analysis and principal component analysis show strong separation of community composition between exposed (modelled wave exposure > 1000 J m −3 ) and sheltered sites (< 1000 J m −3 ) in 2020. This difference is driven by relatively high cover of Porites sp., other massive corals, encrusting corals, soft corals, rubble and dead table corals at sheltered sites versus high cover of pavement and sponges at exposed sites. Total coral cover and rugosity were also higher at sheltered sites. Adding data from previous years shows benthic community shifts from distinct exposure-driven assemblages and high live coral cover in 2006 towards bare pavement, dead Acropora tables and rubble after the 2015/2016 bleaching event. The subsequent recovery trajectories at sheltered and exposed sites are surprisingly parallel and lead communities towards their respective pre-bleaching communities. These results demonstrate that in the absence of human stressors, community patterns on fore reefs are strongly controlled by wave exposure, even during and after widespread coral loss from bleaching events.

The scope and severity of white‐nose syndrome on hibernating bats in North America - Tina L. Cheng; Jonathan D. Reichard; Jeremy T. H. Coleman; Theodore J. Weller; Wayne E. Thogmartin; Brian E. Reichert; Alyssa B. Bennett; Hugh G. Broders; Joshua Campbell; Katherine Etchison; Daniel J. Feller; Richard Geboy; et al. (Conservation Biology, 2021)
Assessing the scope and severity of threats is necessary for evaluating impacts on populations to inform conservation planning. Quantitative threat assessment often requires monitoring programs that provide reliable data over relevant spatial and temporal scales, yet such programs can be difficult to justify until there is an apparent stressor. Leveraging efforts of wildlife management agencies to record winter counts of hibernating bats, we collated data for 5 species from over 200 sites across 27 U.S. states and 2 Canadian provinces from 1995 to 2018 to determine the impact of white‐nose syndrome (WNS), a deadly disease of hibernating bats. We estimated declines of winter counts of bat colonies at sites where the invasive fungus that causes WNS ( Pseudogymnoascus destructans ) had been detected to assess the threat impact of WNS. Three species undergoing species status assessment by the U.S. Fish and Wildlife Service ( Myotis septentrionalis , Myotis lucifugus , and Perimyotis subflavus ) declined by more than 90%, which warrants classifying the severity of the WNS threat as extreme based on criteria used by NatureServe. The scope of the WNS threat as defined by NatureServe criteria was large (36% of Myotis lucifugus range) to pervasive (79% of Myotis septentrionalis range) for these species. Declines for 2 other species ( Myotis sodalis and Eptesicus fuscus ) were less severe but still qualified as moderate to serious based on NatureServe criteria. Data‐sharing across jurisdictions provided a comprehensive evaluation of scope and severity of the threat of WNS and indicated regional differences that can inform response efforts at international, national, and state or provincial jurisdictions. We assessed the threat impact of an emerging infectious disease by uniting monitoring efforts across jurisdictional boundaries and demonstrated the importance of coordinated monitoring programs, such as the North American Bat Monitoring Program (NABat), for data‐driven conservation assessments and planning.

Larval cross‐shore transport estimated from internal waves with a background flow: The effects of larval vertical position and depth regulation - Jessica C. Garwood; Andrew J. Lucas; Perry Naughton; Paul L. D. Roberts; Jules S. Jaffe; Laura deGelleke; Peter J. S. Franks (Limnology and Oceanography, 2021)
Cross‐shore velocities in the coastal ocean typically vary with depth. The direction and magnitude of transport experienced by meroplanktonic larvae will therefore be influenced by their vertical position. To quantify how swimming behavior and vertical position in internal waves influence larval cross‐shore transport in the shallow (~ 20 m), stratified coastal waters off Southern California, we deployed swarms of novel, subsurface larval mimics, the Mini‐Autonomous Underwater Explorers (M‐AUEs). The M‐AUEs were programmed to maintain a specified depth, and were deployed near a mooring. Transport of the M‐AUEs was predominantly onshore, with average velocities up to 14 cm s −1 . To put the M‐AUE deployments into a broader context, we simulated > 500 individual high‐frequency internal waves observed at the mooring over a 14‐d deployment; in each internal wave, we released both depth‐keeping and passive virtual larvae every meter in the vertical. After the waves' passage, depth‐keeping virtual larvae were usually found closer to shore than passive larvae released at the same depth. Near the top of the water column (3–5‐m depth), ~ 20% of internal waves enhanced onshore transport of depth‐keeping virtual larvae by ≥ 50 m, whereas only 1% of waves gave similar enhancements to passive larvae. Our observations and simulations showed that depth‐keeping behavior in high‐frequency internal waves resulted in enhanced onshore transport at the top of the water column, and reduced offshore dispersal at the bottom, compared to being passive. Thus, even weak depth‐keeping may allow larvae to reach nearshore adult habitats more reliably than drifting passively.

Responses of ichthyoplankton assemblages to the recent marine heatwave and previous climate fluctuations in several Northeast Pacific marine ecosystems - Jens M. Nielsen; Lauren A. Rogers; Richard D. Brodeur; Andrew R. Thompson; Toby D. Auth; Alison L. Deary; Janet T. Duffy‐Anderson; Moira Galbraith; J. Anthony Koslow; R. Ian Perry (Global Change Biology, 2021)
The effects of climate warming on ecosystem dynamics are widespread throughout the world's oceans. In the Northeast Pacific, large‐scale climate patterns such as the El Niño/Southern Oscillation and Pacific Decadal Oscillation, and recently unprecedented warm ocean conditions from 2014 to 2016, referred to as a marine heatwave (MHW), resulted in large‐scale ecosystem changes. Larval fishes quickly respond to environmental variability and are sensitive indicators of ecosystem change. Categorizing ichthyoplankton dynamics across marine ecosystem in the Northeast Pacific can help elucidate the magnitude of assemblage shifts, and whether responses are synchronous or alternatively governed by local responses to regional oceanographic conditions. We analyzed time‐series data of ichthyoplankton abundances from four ecoregions in the Northeast Pacific ranging from subarctic to subtropical: the Gulf of Alaska (1981–2017), British Columbia (2001–2017), Oregon (1998–2017), and the southern California Current (1981–2017). We assessed the impact of the recent (2014–2016) MHW and how ichthyoplankton assemblages responded to past major climate perturbations since 1981 in these ecosystems. Our results indicate that the MHW caused widespread changes in the ichthyoplankton fauna along the coast of the Northeast Pacific Ocean, but impacts differed between marine ecosystems. For example, abundances for most dominant taxa were at all‐time lows since the beginning of sampling in the Gulf of Alaska and British Columbia, while in Oregon and the southern California Current species richness increased as did abundances of species associated with warmer waters. Lastly, species associated with cold waters also increased in abundances close to shore in southern California during the MHW, a pattern that was distinctly different from previous El Niño events. We also found several large‐scale, synchronized ichthyoplankton assemblage composition shifts during past major climate events. Current climate projections suggest that MHWs will become more intense and thus our findings can help project future changes in larval dynamics, allowing for improved ecosystem management decisions.

St. Helena: An Important Reproductive Habitat for Whale Sharks (Rhincodon typus) in the Central South Atlantic - Cameron T. Perry; Elizabeth Clingham; D. Harry Webb; Rafael de la Parra; Simon J. Pierce; Annalea Beard; LeeAnn Henry; Beth Taylor; Kenickie Andrews; Rhys Hobbs; Gonzalo Araujo; Alistair D. M. Dove (Frontiers in Marine Science, 2020)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Resolving marine dissolved organic phosphorus ( DOP ) composition in a coastal estuary - Douglas W. Bell; Perry J. Pellechia; Ellery D. Ingall; Claudia R. Benitez‐Nelson (Limnology and Oceanography, 2020)
A mechanistic understanding of dissolved organic phosphorus (DOP) utilization, and its role in the marine P cycle, requires knowledge of DOP molecular composition. In this study, a recently developed approach coupling electrodialysis and reverse osmosis with solution 31 P‐NMR analysis was used to examine DOP composition within a tidally dominated salt‐marsh estuary (North Inlet, South Carolina) over seasonal and tidal time frames. The isolation technique allowed for near complete recovery of the DOP pool (90% ± 13%; n = 12) with six broad compound classes quantified: phosphonates, phosphomonoesters, phosphodiesters, pyrophosphate, di‐ and tri‐phosphate nucleotides (nucleoP α ), and polyphosphate. Our results indicate that phosphomonoesters (ca. 61%) and phosphodiesters (ca. 31%) comprise the majority of the DOP pool, with relatively small contributions from pyrophosphates (ca. 4%), phosphonates (ca. 2%), nucleoP α (ca. 1%), and polyphosphates (ca. 1%). The study found no significant differences in DOP composition or concentration between tidal stages, despite significant tidal changes in dissolved organic nitrogen (DON):DOP stoichiometry. Significant seasonal variation was observed, with higher concentrations of phosphonates, nucleoP α , and monophosphates and lower phosphomonoester concentrations in Fall relative to all other seasons. We hypothesize that these seasonal variations reflect the balance between specific compound class seasonal production, lability, and local P demands associated with marine vs. terrestrial sources. Our results indicate that DOP composition exists at a dynamic equilibrium that is strongly conserved across diverse marine environments.

A novel cross‐shore transport mechanism revealed by subsurface, robotic larval mimics: Internal wave deformation of the background velocity field - Jessica C. Garwood; Andrew J. Lucas; Perry Naughton; Matthew H. Alford; Paul L. D. Roberts; Jules S. Jaffe; Laura deGelleke; Peter J. S. Franks (Limnology and Oceanography, 2020)
Coastal physical processes are essential for the cross‐shore transport of meroplanktonic larvae to their benthic adult habitats. To investigate these processes, we released a swarm of novel, trackable, subsurface vehicles, the Mini‐Autonomous Underwater Explorers (M‐AUEs), which we programmed to mimic larval depth‐keeping behavior. The M‐AUE swarm measured a sudden net onshore transport of 30–70 m over 15–20 min, which we investigated in detail. Here, we describe a novel transport mechanism of depth‐keeping plankton revealed by these observations. In situ measurements and models showed that, as a weakly nonlinear internal wave propagated through the swarm, it deformed surface‐intensified, along‐isopycnal background velocities downward, accelerating depth‐keeping organisms onshore. These higher velocities increased both the depth‐keepers' residence time in the wave and total cross‐shore displacement, leading to wave‐induced transports twice those of fully Lagrangian organisms and four times those associated with the unperturbed background currents. Our analyses also show that integrating velocity time series from virtual larvae or mimics moving with the flow yields both larger and more accurate transport estimates than integrating velocity time series obtained at a point (Eulerian). The increased cross‐shore transport of organisms capable of vertical swimming in this wave/background‐current system is mathematically analogous to the increase in onshore transport associated with horizontal swimming in highly nonlinear internal waves. However, the mechanism described here requires much weaker swimming speeds (mm s −1 vs. cm s −1 ) to achieve significant onshore transports, and meroplanktonic larvae only need to orient themselves vertically, not horizontally.

A multidisciplinary-based conceptual model of a fractured sedimentary bedrock aquitard: improved prediction of aquitard integrity - Anthony C. Runkel; Robert G. Tipping; Jessica R. Meyer; Julia R. Steenberg; Andrew J. Retzler; Beth L. Parker; Jeff A. Green; John D. Barry; Perry M. Jones (Hydrogeology Journal, 2018)

Nitrogen isotope (δ 15 N) patterns for amino acids in lemur bones are inconsistent with aridity driving megafaunal extinction in south‐western Madagascar - Sean W. Hixon; Emma A. Elliott Smith; Brooke E. Crowley; George H. Perry; Jeannot Randrianasy; Jean Freddy Ranaivoarisoa; Douglas J. Kennett; Seth D. Newsome (Journal of Quaternary Science, 2018)
Most endemic species with body masses >10 kg on Madagascar went extinct within the past 1000 years. The extent to which human predation, anthropogenic landscape transformation and aridification may separately or together explain this extinction pattern remains controversial. We present nitrogen isotope (δ 15 N) values of individual amino acids preserved in bones from now‐extinct Pachylemur insignis and extant Propithecus verreauxi from two subfossil sites in south‐western Madagascar: Tsirave and Taolambiby. The amino acid‐specific approach allows us to identify environmental signals that are otherwise difficult to recognize in bulk collagen δ 15 N values. Specifically, we use the δ 15 N values of source amino acids (phenylalanine and lysine) as a proxy for habitat aridity between ca . 4000 years ago and present and the spacing of δ 15 N values between trophic and source amino acids to quantify trophic levels for these two lemur species. Despite paleoenvironmental evidence for lowering water tables and the expansion of relatively arid savanna between 4000 and 1000 years ago, our isotope data suggest that these lemurs did not live in increasingly arid habitats and did not change their trophic level. Together, our results support the hypothesis that aridity alone did not play a major role in late Holocene megafaunal extinctions in south‐western Madagascar.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Methyl isonicotinate — a non-pheromone thrips semiochemical — and its potential for pest management - D. A. J. Teulon; M. M. Davidson; N. B. Perry; M. -C. Nielsen; C. Castañé; D. Bosch; J. Riudavets; R. W. H. M. van Tol; W. J. de Kogel (International Journal of Tropical Insect Science, 2017)

Salbutamol effects on systemic potassium dynamics during and following intense continuous and intermittent exercise - Muath M. Altarawneh; Aaron Petersen; Robert Smith; David M. Rouffet; Francois Billaut; Ben D. Perry; Victoria L. Wyckelsma; Antony Tobin; Michael J. McKenna (European Journal of Applied Physiology, 2016)

Long-Term Trends of Nutrients and Phytoplankton in Chesapeake Bay - L. W. Harding; C. L. Gallegos; E. S. Perry; W. D. Miller; J. E. Adolf; M. E. Mallonee; H. W. Paerl (Estuaries and Coasts, 2016)

Prediction of the Export and Fate of Global Ocean Net Primary Production: The EXPORTS Science Plan - David A. Siegel; Ken O. Buesseler; Michael J. Behrenfeld; Claudia R. Benitez-Nelson; Emmanuel Boss; Mark A. Brzezinski; Adrian Burd; Craig A. Carlson; Eric A. D'Asaro; Scott C. Doney; Mary J. Perry; Rachel H. R. Stanley; et al. (Frontiers in Marine Science, 2016)

A genetic discontinuity in moose (Alces alces) in Alaska corresponds with fenced transportation infrastructure - Robert E. Wilson; Sean D. Farley; Thomas J. McDonough; Sandra L. Talbot; Perry S. Barboza (Conservation Genetics, 2015)

The Y ersinia pestis HmsCDE regulatory system is essential for blockage of the oriental rat flea ( X enopsylla cheopis ), a classic plague vector - Alexander G. Bobrov; Olga Kirillina; Viveka Vadyvaloo; Benjamin J. Koestler; Angela K. Hinz; Dietrich Mack; Christopher M. Waters; Robert D. Perry (Environmental Microbiology, 2015)
Summary The second messenger molecule cyclic diguanylate is essential for Y ersinia pestis biofilm formation that is important for blockage‐dependent plague transmission from fleas to mammals. Two diguanylate cyclases ( DGCs ) HmsT and Y 3730 ( HmsD ) are responsible for biofilm formation in vitro and biofilm‐dependent blockage in the oriental rat flea X enopsylla cheopis respectively. Here, we have identified a tripartite signalling system encoded by the y3729‐y3731 operon that is responsible for regulation of biofilm formation in different environments. We present genetic evidence that a putative inner membrane‐anchored protein with a large periplasmic domain Y 3729 ( HmsC ) inhibits HmsD DGC activity in vitro while an outer membrane P al‐like putative lipoprotein Y 3731 ( HmsE ) counteracts HmsC to activate HmsD in the gut of X . cheopis . We propose that HmsE is a critical element in the transduction of environmental signal(s) required for HmsD ‐dependent biofilm formation.

Evaluation of a new chromogenic medium, chromID OXA-48, for recovery of carbapenemase-producing Enterobacteriaceae from patients at a university hospital in Turkey - P. Zarakolu; K. M. Day; H. E. Sidjabat; W. Kamolvit; C. V. Lanyon; S. P. Cummings; D. L. Paterson; M. Akova; J. D. Perry (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Identification and evaluation of quantitative trait loci underlying resistance to multiple HG types of soybean cyst nematode in soybean PI 437655 - Yongqing Jiao; Tri D. Vuong; Yan Liu; Clinton Meinhardt; Yang Liu; Trupti Joshi; Perry B. Cregan; Dong Xu; J. Grover Shannon; Henry T. Nguyen (Theoretical and Applied Genetics, 2015)

Primates and Cameras - Brian D. Gerber; Perry J. Williams; Larissa L. Bailey (International Journal of Primatology, 2014)

Capsaicin induces apoptosis in human small cell lung cancer via the TRPV6 receptor and the calpain pathway - Jamie K. Lau; Kathleen C. Brown; Aaron M. Dom; Theodore R. Witte; Brent A. Thornhill; Clayton M. Crabtree; Haley E. Perry; J. Michael Brown; John G. Ball; Rebecca G. Creel; C. Luke Damron; William D. Rollyson; et al. (Apoptosis, 2014)

A conceptual framework for predicting temperate ecosystem sensitivity to human impacts on fire regimes - D. B. McWethy; P. E. Higuera; C. Whitlock; T. T. Veblen; D. M. J. S. Bowman; G. J. Cary; S. G. Haberle; R. E. Keane; B. D. Maxwell; M. S. McGlone; G. L. W. Perry; J. M. Wilmshurst; et al. (Global Ecology and Biogeography, 2013)
Aim The increased incidence of large fires around much of the world in recent decades raises questions about human and non‐human drivers of fire and the likelihood of increased fire activity in the future. The purpose of this paper is to outline a conceptual framework for examining where human‐set fires and feedbacks are likely to be most pronounced in temperate forests world‐wide and to establish and test a methodology for evaluating this framework using palaeoecological records. Location T asmania, north‐western USA , southern S outh A merica and N ew Z ealand. Methods We outline a conceptual framework for predicting the sensitivity of ecosystems to human impacts on fire regimes and then use a circum‐ P acific comparison of existing historical reconstructions of fire, climate, human settlement and vegetation to evaluate this approach. Results Previous research investigating important controls on fire activity shows that the sensitivity of temperate ecosystems to human‐set fires is modulated by the frequency of natural fire occurrence, fuel moisture and fuel type and availability. Palaeoecological data from four temperate regions suggest that the effects of anthropogenic burning are greatest where fire is naturally rare, vegetation is poorly adapted to fire and fuel biomass is abundant and contiguous. Alternatively, where fire activity is naturally high and vegetation is well adapted to fire, evidence of human influence on fire and vegetation is less obvious. Main conclusions Palaeofire records suggest that the most dynamic and persistent ecosystem transitions occur where human activities increase landscape flammability through fire–vegetation feedbacks. Rapid forest transitions in biomass‐rich ecosystems such as N ew Z ealand and areas of Tasmania and southern South America illustrate how landscapes experiencing few fires can shift past tipping points to become fire‐prone landscapes with new alternative stable state communities. Comparisons of palaeoecological data from different regions with similar biophysical gradients but different human settlement histories can provide new opportunities for understanding ecosystem vulnerability to fire–climate–human interactions.

Human temperature regulation when given the opportunity to behave - Zachary J. Schlader; Blake G. Perry; M. Rahimi Che Jusoh; Lynette D. Hodges; Stephen R. Stannard; Toby Mündel (European Journal of Applied Physiology, 2013)

Determining the influence of environmental and patient specific factors on the polymicrobial communities of the cystic fibrosis airway - Andrew Nelson; Audrey Perry; John D. Perry; Stephen J. Bourke; Stephen P. Cummings; Anthony De Soyza (Antonie van Leeuwenhoek, 2013)

The controls on phosphorus availability in a Boreal lake ecosystem since deglaciation - Stephen A. Norton; Randall H. Perry; Jasmine E. Saros; George L. Jacobson; Ivan J. Fernandez; Jiří Kopáček; Tiffany A. Wilson; Michael D. SanClements (Journal of Paleolimnology, 2011)

Erratum to: Measuring sediment accretion in early tidal marsh restoration - John Y. Takekawa; Isa Woo; Nicole D. Athearn; Scott Demers; Rachel J. Gardiner; William M. Perry; Neil K. Ganju; Gregory G. Shellenbarger; David H. Schoellhamer (Wetlands Ecology and Management, 2010)

Polyphosphate in Trichodesmium from the low‐phosphorus Sargasso Sea - Elizabeth D. Orchard; Claudia R. Benitez-Nelson; Perry J. Pellechia; Michael W. Lomas; Sonya T. Dyhrman (Limnology and Oceanography, 2010)
Polyphosphate (polyP) is often considered to be the product of luxury uptake in areas of excess phosphorus (P), but can also accumulate in P‐depleted cells in response to P resupply. To test the hypothesis that polyP is present in phytoplankton from oligotrophic systems, the marine diazotroph Trichodesmium was collected from the low‐P surface waters of the Sargasso Sea and assayed with solid‐state 31 P nuclear magnetic resonance spectroscopy. Up to 25% of Trichodesmium cellular P was characterized as polyP, despite physiological data that indicated the colonies were P deplete. This was consistent with culture studies where there were high percentages of polyP under P‐deplete conditions. All Trichodesmium species examined had the genetic machinery to produce and degrade polyP. Trends in the amount of Trichodesmium polyP along the cruise transect showed that allocation of P to polyP was consistently high, and that the ratio of polyP : carbon varied with changes in temperature and mixed‐layer depth. It may be that Trichodesmium was taking advantage of pulses in P supply, and that polyP is a physiological fingerprint of this variability. Additionally, if polyP formation is a common trait in phytoplankton, polyP released from cells could be an additional bioavailable component of the dissolved organic P pool. Taken together, this study highlights the importance of polyP to P cycling and cellular P allocation even in oligotrophic regions.

Measuring sediment accretion in early tidal marsh restoration - John Y. Takekawa; Isa Woo; Nicole D. Athearn; Scott Demers; Rachel J. Gardiner; William M. Perry; Neil K. Ganju; Gregory G. Shellenbarger; David H. Schoellhamer (Wetlands Ecology and Management, 2010)

Improving groundwater resource accounting in irrigated areas : a prerequisite for promoting sustainable use - S. S. D. Foster; C. J. Perry (Hydrogeology Journal, 2010)

Clinical and molecular epidemiology of ciprofloxacin-susceptible MRSA encoding PVL in England and Wales - M. J. Ellington; C. Perry; M. Ganner; M. Warner; I. McCormick Smith; R. L. Hill; L. Shallcross; S. Sabersheikh; A. Holmes; B. D. Cookson; A. M. Kearns (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Effects of 14 days of microgravity on fast hindlimb and diaphragm muscles of the rat - Mark D. Schuenke; David W. Reed; William J. Kraemer; Robert S. Staron; Jeff S. Volek; Wesley C. Hymer; Scott Gordon; L. Perry Koziris (European Journal of Applied Physiology, 2009)

Observations of pigment and particle distributions in the western North Atlantic from an autonomous float and ocean color satellite - E. Boss; D. Swift; L. Taylor; P. Brickley; R. Zaneveld; S. Riser; M. J. Perry; P. G. Strutton (Limnology and Oceanography, 2008)
Profiling floats with optical sensors can provide important complementary data to satellite ocean color determinations by providing information about the vertical structure of ocean waters, as well as surface waters obscured by clouds. Here we demonstrate this ability by pairing satellite ocean color data with records from a profiling float that obtained continuous, high‐quality optical data for 3 yr in the North Atlantic Ocean. Good agreement was found between satellite and float data, and the relationship between satellite chlorophyll and floatderived particulate backscattering was consistent with previously published data. Upper ocean biogeochemical dynamics were evidenced in float measurements, which displayed strong seasonal patterns associated with phytoplankton blooms, and depth and seasonal patterns associated with an increase in pigmentation per particle at low light. Surface optical variables had shorter decorrelation timescales than did physical variables (unlike at low latitudes), suggesting that biogeochemical rather than physical processes controlled much of the observed variability. After 2.25 yr in the subpolar North Atlantic between Newfoundland and Greenland, the float crossed the North Atlantic Current to warmer waters, where it sampled an unusual eddy for 3 months. This anticyclonic feature contained elevated particulate material from surface to 1000‐m depth and was the only such event in the float's record. This eddy was associated with weakly elevated surface pigment and backscattering, but depthintegrated backscattering was similar to that previously observed during spring blooms. Such seldom‐observed eddies, if frequent, are likely to make an important contribution to the delivery of particles to depth.

Introduction to the Limnology and Oceanography Special Issue on Autonomous and Lagrangian Platforms and Sensors (ALPS) - T. D. Dickey; E. C. Itsweire; M. A. Moline; M. J. Perry (Limnology and Oceanography, 2008)
This issue is devoted to recent developments of autonomous and Lagrangian platforms and sensors (ALPS) and their uses for solving a broad range of interdisciplinary aquatic problems. The collective papers treat a variety of problems that generally require measurements spanning a continuum of temporal and spatial scales. ALPS platforms in this issue include surface drifters, profiling and other types of subsurface floats, gliders, unmanned boats, autonomous underwater vehicles, and instrumented animals. ALPS platforms can provide access in difficult environments (e.g., under ice and in high‐sea states). They are also important for emerging networked ocean and lake observing systems that require continuous measurements and near‐real‐time data. This introductory paper provides historical perspectives, background, motivation for the issue, and a tabular summary of papers in the present collection.

An assessment of the suitability of a plastic thermometer screen for climatic data collection - M. C. Perry; M. J. Prior; D. E. Parker (International Journal of Climatology, 2007)
For over a century, wooden thermometer screens of the Stevenson design have been used in the meteorological station network administered by the UK Met Office. A screen is now being manufactured of the same dimensions but made from plastic. This requires minimal maintenance and has the potential for a much longer life than the wooden type. In order to determine whether a changeover to the plastic type would be acceptable for climatological applications, in particular for studies of climate change, a 12‐month trial was carried out at 3 contrasting UK locations. Temperature and relative humidity measurements were made at 1‐minute intervals in plastic and wooden trial screens installed at each site, as well as in the existing operational wooden screens. At the start of the trial, acceptance criteria based on Global Climate Observing System (GCOS) standards were set for mean and extreme temperature values. The temperature differences between the trial wooden and plastic screens were all found to be within these acceptance criteria. The largest differences occurred between pairs of wooden screens, not between wooden and plastic screens. Analysis of humidity differences between wooden and plastic screens did not yield clear results. To help understand the temperature and humidity differences, the screen data were analysed in terms of other current weather conditions, principally solar radiation and wind speed. We recommend that, in temperate climates, the plastic thermometer screen is a climatologically consistent alternative to the wooden design, requiring no adjustments to long‐term records. © Crown Copyright 2006. Reproduced with the permission of the Controller of HMSO. Published by John Wiley & Sons, Ltd.

Greater vulnerability to the amnestic effects of ketamine in males - Celia J. A. Morgan; Edward B. Perry; Hyung-Sang Cho; John H. Krystal; Deepak Cyril D’Souza (Psychopharmacology, 2006)

Escalation of i.v. cocaine self-administration and reinstatement of cocaine-seeking behavior in rats bred for high and low saccharin intake - Jennifer L. Perry; Andrew D. Morgan; Justin J. Anker; Nancy K. Dess; Marilyn E. Carroll (Psychopharmacology, 2006)

The cost of being an omnivore: mandible wear from plant feeding in a true bug - Bernard D. Roitberg; David R. Gillespie; Donald M. J. Quiring; Colleen R. Alma; Wade H. Jenner; Jennifer Perry; Jason H. Peterson; Maxence Salomon; Sherah VanLaerhoven (The Science of Nature, 2005)

Assessment of prey overlap between a native ( Polistes humilis ) and an introduced ( Vespula germanica ) social wasp using morphology and phylogenetic analyses of 16S rDNA - Marta L. Kasper; Andrew F. Reeson; Steven J. B. Cooper; Kym D. Perry; Andrew D. Austin (Molecular Ecology, 2004)
In newly invaded communities, interspecific competition is thought to play an important role in determining the success of the invader and its impact on the native community. In southern Australia, the native Polistes humilis was the predominant social wasp prior to the arrival of the exotic Vespula germanica (Hymenoptera: Vespidae) . Both species forage for similar resources (water, pulp, carbohydrate and protein prey), and concerns have arisen about potential competition between them. The aim of this study was to identify the protein foods that these wasps feed on. As many prey items are masticated by these wasps to the degree that they cannot be identified using conventional means, morphological identification was complemented by sequencing fragments of the mitochondrial 16S rRNA gene. GenBank searches using blast and phylogenetic analyses were used to identify prey items to at least order level. The results were used to construct complete prey inventories for the two species. These indicate that while P. humilis is restricted to feeding on lepidopteran larvae, V. germanica collects a variety of prey of invertebrate and vertebrate origin. Calculated values of prey overlap between the two species are used to discuss the implications of V. germanica impacting on P. humilis. Results obtained are compared to those gained by solely ‘conventional’ methods, and the advantages of using DNA‐based taxonomy in ecological studies are emphasized.

Adventiously-bound redox active iron and copper are at the center of oxidative damage in Alzheimer disease - George Perry; Marta A. Taddeo; Robert B. Petersen; Rudy J. Castellani; Peggy L.R. Harris; Sandra L. Siedlak; Adam D. Cash; Quan Liu; Akohiko Nunomura; Craig S. Atwood; Mark A. Smith (BioMetals, 2003)

DIETS OF FIN, SEI, AND SPERM WHALES IN BRITISH COLUMBIA: AN ANALYSIS OF COMMERCIAL WHALING RECORDS, 1963–1967 - Rowenna D. Flinn; Andrew W. Trites; Edward J. Gregr; R. Ian Perry (Marine Mammal Science, 2002)
A bstract Diets of fin ( Balaenoptera physalus ), sei ( Balaenoptera borealis ), and sperm whales ( Physeter macrocephalus ) were estimated from the stomach contents of individuals killed along the British Columbia coast from 1963 to 1967. The dominant prey types of fin whales were euphausiids, with minor contributions from copepods and fish. Sei whale stomachs contained primarily copepods in three years, whereas euphausiids or a variety of fish dominated the diet in the other two years. Sperm whales consumed primarily North Pacific giant squid ( Moroteuthis robusta ), but secondary prey differed between males and females. Female sperm whales frequently consumed ragfish ( Icosteus spp.) and other fish, whereas the male diet also contained rockfish ( Sebastes spp.). The high abundance of euphausiids along the British Columbia coast likely contributed to the presence of a summer resident population of fin whales. The high abundance of large copepods farther north probably influenced the migration of sei whales through the offshore waters of British Columbia. Sperm whale stomach contents differed by sex reflecting location and possibly breeding behaviors.

Population-Based Evaluation of the Ehrlichia Ruminantium MAP 1B Indirect ELISA - Trevor F. Peter; Christopher J. O'Callaghan; Graham F. Medley; Brian D. Perry; Shalt M. Semu; Suman M. Mahan (Experimental and Applied Acarology, 2001)

The effects of 10 days of spaceflight on the shuttle Endeavour on predominantly fast-twitch muscles in the rat - William J. Kraemer; Robert S. Staron; Scott E. Gordon; Jeff S. Volek; L. Perry Koziris; Noel D. Duncan; Bradley C. Nindl; Ana L. Gómez; James O. Marx; Andrew C. Fry; Jerry D. Murray (Histochemistry and Cell Biology, 2000)

Sex differences in sensorimotor gating of the human startle reflex: all smoke? - N. R. Swerdlow; M. A. Geyer; P. L. Hartman; J. Sprock; P. P. Auerbach; K. Cadenhead; W. Perry; D. L. Braff (Psychopharmacology, 1999)

Biopharmaceutical Approaches for Developing and Assessing Oral Peptide Delivery Strategies and Systems: In Vitro Permeability and In Vivo Oral Absorption of Salmon Calcitonin - Patrick J. Sinko; Yong-Hee Lee; Vijaya Makhey; Glen D. Leesman; John P. Sutyak; Hongshi Yu; Barbara Perry; Curtis L. Smith; Peidi Hu; Erik J. Wagner; Lisa M. Falzone; Laura T. McWhorter; et al. (Pharmaceutical Research, 1999)

Sequence-tagged-site (STS) markers of arbitrary genes: the utility of black spruce-derived STS primers in other conifers - D. J. Perry; J. Bousquet (Theoretical and Applied Genetics, 1998)

DNA Isolation and AFLP™ Genetic Fingerprinting of shape Theobroma cacao (L.) - Matthew D. Perry; Michael R. Davey; J. Brian Power; Kenneth C. Lowe; H. Frances J. Bligh; Paul S. Roach; Chris Jones (Plant Molecular Biology Reporter, 1998)

CDP840 - M. J. Perry; J. O’Connell; C. Walker; T. Crabbe; D. Baldock; A. Russell; S. Lumb; Z. Huang; D. Howat; R. Allen; M. Merriman; J. Walls; et al. (Cell Biochemistry and Biophysics, 1998)

The 10th Conference of the Entomological Society of Israel - Rachel Galun; I. Ishaaya; Sara Yablonski; Zmira Mendelson; Y. Mansour; Svetlana Kontsedalov; U. Pluschkell; A. R. Horowitz; A. R. Horowitz; Sara Yablonski; Zmira Mendelson; I. Ishaaya; et al. (Phytoparasitica, 1997)

Effects of Land‐Use and Tsetse Fly Control on Bird Species Richness in Southwestern Ethiopia - Cathleen J. Wilson; Robin S. Reid; Nancy L. Stanton; Brian D. Perry (Conservation Biology, 1997)
Successful control of tsetse (Glossina spp.)‐transmitted trypanosomiasis in the Ghibe Valley, Ethiopia, appears to have accelerated conversion of wooded grassland into cropland. Land conversion, in turn, may have fragmented wildlife habitat. Our objective was to assess the influence of the expansion of agricultural land‐use, brought about by tsetse control, on ecological properties by using bird species richness and composition as indicators of environmental impacts. We sampled bird species richness and composition (using Timed‐Species counts) and habitat structure (using field sampling and remote sensing) in four land cover/land‐use types in areas subjected to tsetse fly control and adjacent areas without control. At the height of the growing season bird species numbers and vegetative complexity were greater in the small‐holder, oxen‐plowed fields and riparian woodlands than in wooded grasslands or in large‐holder, tractor‐plowed fields. Species composition was highly dissimilar (40–70% dissimilarity) comparing among land‐use types, with many species found only in a single type. This implies that trypanosomiasis control that results in land conversion from wooded grasslands to small‐holder farming in this region may have no adverse impacts on bird species numbers but will alter composition. These results also suggest that moderate land‐use by humans (e.g., small‐holder field mosaics) increases habitat heterogeneity and bird species richness relative to high levels of use (e.g., tractor‐plowed fields). Tsetse control may be indirectly maintaining species richness in the valley by encouraging the differential spread of these small‐scale, heterogeneous farms in place of large‐scale, homogeneous farms. Nevertheless, if the extent of small‐holder farms significantly exceeds that of present levels, negative impacts on bird species richness and large shifts in species composition may occur.

Changes in mutagenicity during crude oil degradation by fungi - Linda E. Rudd; Jerome J. Perry; Virginia S. Houk; Ron W. Williams; Larry D. Claxton (Biodegradation, 1996)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)